Perbedaan Kualitas Tidur Mahasiswa yang Merokok dengan yang Tidak Merokok di Fakultas Sastra dan Seni Rupa Universitas Sebelas Maret - Saputri, Rizky Hening; Fanani, M.; Hanim, Diffah (Nexus Kedokteran Klinik, 2014)
Background: Smoking was a bad habit that has been a problem throughout the world both in developed and developing countries. Primary Health Research mentioned that 27.2% smokers were male students and moreover smoking habit of students was followed by staying up late at night. Smokers who did smoke activity at night have higher risk of experiencing sleep disturbances than smokers who did smoke activity during the day. Approximately 20% to 50% adults per year report sleep disturbance fulfillment and about 17% had serious sleep disturbance fulfillment experience. The current prevalence of insomnia according to DSM-IV criteria in adolescents showed 10.7%. These number would be increase along with the increase of age and contributing factors like smoking. This study aims to determine the difference of sleep quality between smoker and non-smoker college student in the Faculty of Letter and Art Sebelas Maret University. Method: Observational analytic with cross sectional method approach. Samples taken by Purposive Random Sampling method. The number of sample was 100 consisted of 50 male smoker students and 50 male non-smoker students. This research instrument was smoking activity questionnaire, LMMPI questionnaire and PSQI questionnaire. Data analysis done with independent T-test. Result: The results showed 39 (64%) samples of male smoker students had poor sleep quality, and 11 (28,2%) samples of male smoker students had good sleep quality. While the male non-smoker 28 (71,8%) samples had good sleep quality and 22 (36%) samples of male non-smokers students had poor sleep quality. T Count value (-3.487) < t table value (-1.661) with p = 0.001. Conclusion: There was difference in the sleep quality between smoker and non-smoker college student in the Faculty of Letter and Art Sebelas Maret University (p = 0.001). Some smoker college student had poor sleep quality while non-smoker college student had good sleep quality. Keywords: Smoker, Non- smoker, sleep quality.Â